Flow cytogenetics - Gray, Joe W. (Analytical cytology series., 1989)
This is the first book to be devoted entirely to the application and development of flow techniques in cytogenetics. It provides comprehensive information on the use of flow cytometry and sorting for chromosome classification and purification. Cytogenetics and molecular biologists will find this book an invaluable reference source. Key Features * Practical details for the preparation and analysis of chromosomes using flow cytometry * Flow karyotyping for sensitive rapid analysis of chromosome normality and the detection of aberrant chromosomes * Flow sorting as a source of chromosome-specific DNA for gene mapping and recombinant DNA libraries * Construction and current status of chromosome-specific recombinant DNA libraries.